BOVINE SUBCLINICAL MASTITIS: BACTERIAL ISOLATION AND PHAGE TYPING OF STAPHYLOCOCCUS AUREUS ISOLATES - A.AL-Izzi, S.; K. Abo, N.; A. AL-Azawi, W. (The Iraqi Journal of Veterinary Medicine, 1989)
Out of 107 COW milk samples, 44(41.12%) yielded bacterial growth. The isolates were identified according to their cultural, morphological and biochemical characteristics as Staphylococcus aureus (40.91%).. Escherichia coli (29.55%), Staphylococcus epidermidis (18.18%), Streptococcus uberis (9.09%) and Corynebacterium pyogenes (2.29%). Out of 18 Staphylococcus aureus isolates, ten (55.56%) were typable with a set of 23 human phages. These isolates were lysed by three or more phages. The most effective antimicrobial agents against the majority of of Staphylococcus aureus isolates were : erythromycin, rifampicin, gentamicin, chloramphenicol, carbenicillin, cloxacillin, ampicillin, cephalothin and tetracycline as indicated by in vitro sensitivity test.